The Pleasure Of Being Human - Nargiza Shoaliyeva PhD (Genius Journals, 2024)
There are many poets and poetesses in modern Uzbek literature, but the name of the daughter of the beautiful valley, Farida Afruz, who is liked by our people and whose words are in the hearts of people, attracts special attention. The poems of our poetess illuminate our world in accordance with her pseudonym, and the philosophical meaning of the poems gives purity and light to our hearts. The article attempts to understand the essence of the poetess's work through an artistic analysis of some poems
Keywords: Farida Afruz; poem; verse